Rich Harvest and Few Laborers: The Challenges and Opportunities of Priestly Life and Ministry in the Roman Catholic Ecclesiastical Province of Kingston - Ajawara, Cosmas (Université Saint-Paul / Saint Paul University, 2018)
Most of the systematic studies done on the priesthood in North America in the last fifty years were conducted in the United States. To date, no such study exists in Canada. By replicating many of the questions used in the 2009 study of the priesthood by Mary Gautier et al., this researcher investigated the experiences and trends in priestly life and ministry within the Canadian context. This research was conducted based on the researcher's conviction that there are many challenges and opportunities facing the priesthood and pastoral ministry in the ecclesiastical province of Kingston since the close of the Second Vatican Council. This project explores the experiences of priests in ministry within this province in order to establish these challenges and opportunities in pastoral ministry. The aim is to offer some necessary insights, pathways, and benchmarks to be considered in the possible revision of the ministry of the ordained in the four dioceses that make up the ecclesiastical province of Kingston. The result of this study, obtained after a careful analysis of the data collected through surveys and follow-up interviews reveals the existence of some changes in the social characteristics of priests in ministry in the ecclesiastical province of Kingston. The experiences of priests in the study also indicate that priests in ministry face significant challenges and problems in the exercise of their ministry. However, irrespective of these challenges and problems, this research also finds that ministry in today's Church presents enormous opportunities for growth and development, especially in the area of lay ministry. The study findings and recommendations will assist the local churches and the local bishops to meet their pastoral responsibilities and duties toward ordained and lay ministry in the Church.
Keywords: Priesthood; Priestly Life; Ministry; Lay; Challenges; Opportunities.